Shariah And Legal Frameworks Of The Shariah Committee In The Islamic Financial Institutions In Malaysia - Zulkifli Hasan; Norfadhilah Mohamad Ali; Syaryanti Hussin (Universiti Sains Islam Malaysia, 2024)
The d evelopment of I slamic b anking and finance s ector i n M alaysia needs support infrastructure and one of the most important structures is the Shariah Committee. Good governance of the Shariah Committee is the very essence in the development of Islamic banking and finance sector in Malaysia. The Shariah Committee normally consists offiqh scholars, practitioners and academicians with knowledge and expertise in Islamic jurisprudence in order to advise Islamic financial institutions on the shariah compliance in all aspects and its operations. This research explores the shariah and legal frameworks of the Shariah Committee of Islamic financial institution in Malaysia with reference to the relevant statutory legislation, Central Bank of Malaysia's Guidelines and Procedures including interviews with the practitioners and distributing questionnaires. It is submitted that Malaysia has set up an effective frameworks in the implementation of Islamic banking and finance and this research offers some recommendations for further improvement.